Foreground and background detection of thermal image for h1ni screening - Nur Syazreen, Ardnan (2012)
The thermal imaging cameras used in airports are specifically designed to detect anyone with a higher than normal body temperature in a subtle and non invasive way. The cameras are able to gather information on an individual’s body temperature in a matter of seconds allowing airport officials to vastly narrow down possible carriers of the diseases and help avoid a flu pandemic. The cameras produce infrared images of peoples and detects if the temperature falls within a certain acceptable range. The dissertation objective is to design software to automatically detect the people in the image. Using image pre-processing technique which background-subtraction to remove the background of the image and by using image processing technique such as thresholding and morphology, to detect the foreground of the image which are the peoples, filling, lining and some more techniques, FGdetection.m is the execution file in MATLAB that takes the input image and output the image with detected peoples.